PENGENDALIAN KUALITAS PRODUK CEPLIS DENGAN PENDEKATAN SIX SIGMA DAN KAIZEN - ramayanti, gina; Laila Latisa (Prodi Teknik Industri, Fakultas Teknik, 2025)
This research was conducted at PT. Sartika Barka Berlimpah which is one of the centers for typical Cilegon souvenirs and one type of product that is prepared with processed melinjo, namely ceplis. In the original ceplis production process at this company, there are often product defects with the types of defects, namely texture, color and oiliness. In the production process, this company has not implemented six sigma, so there is no measurement of the sigma level. If you continue to ignore it, it will have a detrimental impact on the company, such as increasing operational costs and decreasing profits. This research aims to improve the quality of ceplis products so that losses from production can be reduced, as well as to determine the characteristics of product defects that occur. This research uses the six sigma method with a kaizen approach. The results of this research are that the average Defect Per Million Opportunities (DPMO) value in the July- December 2023 period is 17245.76 with a sigma value of 3.61 which is in the industry average category. The highest defects in ceplis products are defects in texture and color. Based on the Five M-Checklist analysis, to overcome the quality of ceplis products, this can be done by providing a break of 5-10 minutes for rest at 9.30 and 15.30, more thorough and stringent inspections for the quality of melinjo seeds, providing a stainless-steel oil container next to the fryer, and carry out routine cleaning of the melinjo seed storage area every week.